APPROACHES TO POST-OPERATIVE PAIN RELIEF DURING TOTAL KNEE AND HIP REPLACEMENT - A. V. Kurganskiy; K. N. Khrapov (Вестник анестезиологии и реаниматологии, 2018)
The review describes modern approaches to pain relief in the patients after total knee and hip replacement. It covers the principles of multi-modal analgesia, benefits and drawbacks of such ways of pain relief as intravenous analgesia with opioids, spinal and epidural analgesia; it compares different variants of peripheral blocks, and puts some light on a relatively new method of local periarticular infiltration anesthesia.The authors agree that further research is needed to optimize post-operative pain relief after total knee and hip replacement.